Economic and Social Dimensions of Migration from the Countryside to the Cities in Turkey 1950 – 1980 (Historical study) - Shekho, Tareq A. (Humanities Journal of University of Zakho, 2016)
The rural immigration is one of the social and economic problems because of its negative effects on both rural and sedentary life as well. This problem has economic effects reflected on the social aspect and on both individual and society as a whole. This took place in Turkey which witnessed a widespread rural immigration. In fact, this immigration started in 1935 but in a very slow and limited way. However during the fifteenth and with industrialization under the rule of the Democratic Party Government 1950 – 1960, when the government started putting new policies to develop Turkey economically, Which resorted to build many factories, companies and establishment in different periods which contributed to attract rural inhabitants who suffered from unemployment because of using modern machinery in agriculture. Therefore, the effects of the rural emigration to cities were reflected at all levels particularly the economic and social ones. Accordingly, it might be possible to know the main reasons and factors behind this increasing emigration especially to Ankara and Istanbul. Consequently, this immigration had negative effects on the mentioned levels which became later the main reasons for the economic and social crisis witnessed by Turkey during the seventieth when this crisis deteriorated.